2019
DOI: 10.3171/2018.11.focus18517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of revascularization on cognitive outcomes in intracranial steno-occlusive disease: a systematic review

Abstract: OBJECTIVESteno-occlusive diseases of the cerebral vasculature have been associated with cognitive decline. The authors performed a systematic review of the existing literature on intracranial steno-occlusive disease, including intracranial atherosclerosis and moyamoya disease (MMD), to determine the extent and quality of evidence for the effect of revascularization on cognitive performance.METHODSA systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Despite the apparent relationship between severe steno-occlusive disease and cognitive impairment, prospective studies of carotid revascularization have not demonstrated any impact on cognitive performance measures. 16 The currently enrolling Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis Trial-2 is evaluating cognitive function as a secondary end point and may shed more insight on the impact of such procedures. 17 This case series highlights the importance of considering chronic hypoperfusion and large vessel stenosis in patients presenting with clinical syndromes consistent with a neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent relationship between severe steno-occlusive disease and cognitive impairment, prospective studies of carotid revascularization have not demonstrated any impact on cognitive performance measures. 16 The currently enrolling Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis Trial-2 is evaluating cognitive function as a secondary end point and may shed more insight on the impact of such procedures. 17 This case series highlights the importance of considering chronic hypoperfusion and large vessel stenosis in patients presenting with clinical syndromes consistent with a neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that endovascular embolization is safe and efficacious for treating intracranial aneurysm with liquid embolic agents or coils in most locations in patients with MMD [ 173 , 174 ]. Moreover, some studies [ 175 , 176 ] have reported that while EVT can be applied in atherosclerotic moyamoya syndrome, it is a major challenge to perform EVT for MMD in stenosed arteries in which super-selective catheterization is technically difficult [ 177 ]. Indeed, there are plenty of attempts to treat MMD by EVT in order to improve forward blood flow of target vessels.…”
Section: Treatmentmentioning
confidence: 99%
“…Cerebral hypoperfusion induced by steno-occlusive diseases has been thought to be associated with cognitive decline [10][11][12]. If so, the status of cerebral hemodynamics (especially stage 2) may be estimated using cognitive function tests.…”
Section: Introductionmentioning
confidence: 99%
“…If so, the status of cerebral hemodynamics (especially stage 2) may be estimated using cognitive function tests. Some previous reports suggested that EC-IC bypass improves cognitive function in patients with steno-occlusive disease [ 11 , 12 ]. However, these previous studies have some limitations, and the effect of EC-IC bypass on cognitive function has remained controversial [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%